Government Strategy to Recover the Tourism Sector Affected by the Covid-19 Pandemic - Apriyanti, Masayu Endang (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The Covid-19 pandemic hit the world including Indonesia, in a period of approximately 2 years, pandemic had negative impact. One of the businesses that was greatly affected was the tourism sector in Indonesian provinces, some were still able to survive, but some were not, due to sluggish demand for the tourism sector, the implementation of the PPKM (Implementation of Community Activity Restrictions) policy, prohibiting crowds, and even being prohibited from leaving the house if it's not an emergency, of course all of that has impact on the wheels of the economy temporarily, but the cost of living must still run. This study analyzes secondary data from news, books, scientific journals and data published by government. The point of the finding is that pandemic has had major impact on tourism sector. Because during the pandemic, many activities were online, thus reducing the number of tourist visits and that had impact on incoming income. Because changes in the way of transactions can reduce customer interest, inflation reduces people's purchasing power, and number of unemployed increases because many businesses are not operational, this causes economy to decline. The government must have best strategy to stabilize the wheels of the economy, indeed, it is not easy, there must be a big struggle and hard effort to rise, it can be through the policies & regulations that are enforced, the spirit of fighting, supporting each other according to each other's roles & responsibilities, so that the economy recovered.